Promotion of skills related to computational thinking through project-based learning (GEON Journal (Management, Organizations and Business), 2021)
Problematic: The greater complexity of current problems demands that students strengthen their skills related to problem solving. If we teach students to solve problems, they will gain independence and confidence to face future challenges. Goals: This project focuses on promoting computational thinking skills through project development. Materials and methods: The students worked on the development of team projects, using roles. During their development, the students had to process information, model the initial prototypes, evaluate flaws, and incorporate original ideas based on their own creative processes. Results: The results show that the main challenge identified by the students was to generate agreements within the groups that would allow them to adjust the prototypes and reach their final versions. Discussion: In this project, the students were exposed to situations that emulated real work environments, where they had to develop consensus while identifying a systematic route to solve problems. Conclusions: This type of project creates an ideal space for students to assume roles, communicate efficiently, learn from each other, and develop innovative solutions in a real collaborative learning environment. Contribution/originality: This project will allow teachers to have a problem-solving methodology that they can share with their students so that they can apply it to solving problems by emulating situations that students will encounter during their professional and personal development.
Keywords: Computational; Problems; Projects; Prototypes; Skills; Solution; Thinking; JEL I21 Analysis of Education